Psychiatric services for adolescents with complex mental health needs : A qualitative study of service user preferences - Strøm, Ingrid Byng; Lexén, Annika; Bonnert, Marianne; Jonsson, Ulf (Clinical Child Psychology and Psychiatry, 2025)
Background: Child and Adolescent Mental Health Services (CAMHS) currently seeks to implement service models that are better suited for young service users with complex mental health needs. This study explored what adolescents view as the key components of a well-functioning contact with CAMHS. Methods: This study was conducted as part of the ongoing implementation of Flexible Assertive Community Treatment (FACT) in the CAMHS in Stockholm, Sweden. Interviews were conducted with 14 adolescents (64% females) aged 14 to 18 (M = 15.78, SD = 1.32) with intensive or longstanding contact with CAMHS. The interviews were analyzed using reflexive thematic analysis. Results: Five key themes were generated: (1) “being involved in my care” – receiving relevant information and being part of important care decisions; (2) “accessing care when I need it” – ensuring services are easily accessible and present in the community; (3) “building a good relationship” – developing strong connections with mental health professionals; (4) “sharing the burden” – improving support and organization to reduce stress related to the healthcare system; and (5) “personalizing my care” – tailoring care to individual preferences and circumstances. Conclusions: The findings emphasize the importance of engaging young service users in developing a mental health service that meets complex needs.
Keywords: Adolescents; CAMHS; FACT; implementation; participation; qualitative study; service user involvement